Observations of near-conjugate high latitude substorms and their low latitude implications - Singh, Anand K.; Jayashree, B.; Sinha, Ashwini K.; Rawat, Rahul; Pathan, B.M.; Dhar, Ajay (2011)
Geomagnetic substorms are triggered on the nightside of the earth's magnetosphere and the most dramatic effect is observed at the auroral latitudes (60°-70° magnetic). Magnetic field disturbances observed at a set of longitudinally distributed auroral stations are used to derive auroral electrojet (AE) indices being widely used to monitor substorm activities. We present observations of magnetic substorms having more prominent effect poleward of the standard auroral oval. Magnetic data from the third Indian Antarctic station, Bharati (BHA; corrected geomagnetic (CGM) coordinates: 74.7°S, 96.6°E) in conjunction with IMAGE chain data (near conjugate station Hornsund (HOR; CGM coordinates: 74.3N, 108.5°E) have been subjected to detailed examination to study such substorms. The substorms presented in this study were mainly localized to high latitudes and hence the standard AE indices failed to monitor such substorm activities. Nevertheless, typical low-latitude features of substorm, for example, positive bay and Pi2 burst on the nightside were distinctly evident.